Estrategias de mejoramiento para incrementar la capacidad de fijacion biologica de nitrogeno del frijol comun en America Latina - Rosas, J.C.; Kipe-Nolt, Judith A.; Henson, R.A.; Bliss, Fredrick A. (1987)
A literature review is presented of the different concepts related to biological N fixation (BNF) in beans as well as the procedures to establish breeding programs leading to increase BNF. The N requirements of bean plants are determined as well as the sources from which it can be obtained; the background and breeding objectives for BNF are also defined. The breeding procedure includes (1) the evaluation of superior genotypes and simultaneous evaluation of Rhizobium strains; (2) the identification of critical factors in making decisions regarding breeding for BNF, such as the variation observed in the interactions between genotypes and Rhizobium strains as well as the methods used to measure that interaction; (3) the development of populations by parent selection as well as the crossing and selection of them by recurrent selection or by the backcrossing and self-pollination method; and (4) the identification of hybrid lines with high BNF capacity and other desirable characteristics, by screening during several generations. Progress obtained regarding breeding of lines with greater BNF capacity are indicated as well as recommendations to establish a breeding program in this field. (CIAT)